Mutant p53 gain of function: repression of CD95(Fas/APO-1) gene expression by tumor-associated p53 mutants - Zalcenstein, Amir; Müller-Schilling, Martina; Krammer, Peter H. (Oncogene, 2003)
Tumor-associated mutant forms of p53 can exert an antiapoptotic gain of function activity, which probably confers a selective advantage upon tumor cells harboring such mutations. We report that mutant p53 suppresses the expression of the CD95 (Fas/APO-1) gene, encoding a death receptor implicated in a variety of apoptotic responses. Moderate (40-50%) downregulation of CD95 mRNA and surface protein expression by mutant p53 correlates with partial protection against CD95-dependent cell death. Excess mutant p53 represses the transcriptional activity of the CD95 promoter, with the extent of repression varying among different tumor-associated p53 mutants. Furthermore, mutant p53 protein binds the CD95 promoter in vitro, in a region distinct from the one implicated in tight interactions of the CD95 gene with wild-type p53. Hence, the CD95 promoter is likely to be a direct target for downregulation by mutant p53. This activity of mutant p53 may contribute to its gain of function effects in oncogenesis.
Gesehen am 07.04.2021